Comparison between cold plasma, electrochemotherapy and combined therapy in a melanoma mouse model. Issue 9 (16th August 2013) - Daeschlein, Georg; Scholz, Sebastian; Lutze, Stine; Arnold, Andreas; von, Sebastian; Kiefer, Thomas; Tueting, Thomas; Hardt, Olaf; Haase, Hermann; Grisk, Olaf; Langner, Sönke; Ritter, Christoph; et al.
Abstract The study was undertaken to compare antitumor efficacy of electrochemotherapy (ECT) with cold plasma therapy (CP) in a melanoma mouse model. After melanoma implantation into the flank of C57BL/6N mice, CP by two different plasma sources (APPJ and DBD) was applied directly to the tumor surface. ECT was performed with bleomycin intravenously at a field strength of 1000 V/cm without or combined with CP. Primary endpoints were tumor growth acceleration (TGA), daily volume progression (DVP) and survival after treatment. Both plasma sources as single treatment showed a significant TGA delay, which proved less effective than ECT. CP (APPJ) combined with ECT (ECJ) significantly improved per cent mouse survival, with significant superiority compared with ECT. Plasma therapy alone albeit less effective seems a potential alternative to ECT in patients with melanoma and can be applied manifold in a session without general anaesthesia. Accordingly, CP alone and combined with ECT may serve as new option in palliative skin melanoma therapy.